Second dorsal metacarpal artery-based index finger dorsal island flap for the management of thumb defects. Issue 1 (January 2022) - Yang, Huan-You; Zhang, Jian-Feng; Huo, Yong-Xin; Wang, Wei; Wang, Bin; Li, Rui-Guo
Summary: Index finger dorsal island flaps were frequently utilized by hand surgeons to reconstruct thumb defects. However, the blood supply of the traditional index finger dorsal island flap comes from the first dorsal metacarpal artery, which has a smaller diameter, more anatomical variation, and can be injured in conjunction with thumb injuries. Therefore, we design an alternative index finger dorsal island flap based on the second dorsal metacarpal artery to treat thumb skin defects. From August 2015 to October 2018, we used the index finger dorsal island flaps with the second dorsal metacarpal artery to treat 11 patients with thumb skin defects. All the flaps and skin grafts survived completely without complications. At the last follow-up, the mean 2PD of the flap was 6.4 mm (45.5% for excellent, 54.5% for good), the mean ROM of the injured thumbs was 115.9° (72.7% for excellent, 27.3% for good), and the mean cosmetics score was 8.6. Our results demonstrate that the index finger dorsal island flap with the second dorsal metacarpal artery is suitable for the reconstruction of thumb skin defects. The flap has an excellent survival rate and good coverage with satisfactory results and represents a promising treatment for the selected patients. Level of Evidence: Therapeutic, level IV